Tinjauan Yuridis Atas Pelaksanaan Pemilu Legislatif Tahun 2014 di Provinsi Kepulauan Riau - Rina Shahriyani Shahrullah; Wagiman Wagiman; Rendra Topan (Fakultas Hukum, Universitas Internasional Batam, 2017)
Elections , which is a means of implementing the people's sovereignty is exercised directly, free, general, secret, honest, and fair within the unitary State of the Republic of Indonesia based on Pancasila and the Law – the Constitution of the Republic of Indonesia in 1945 and is an important component in the democracies adhere to the system of representation. Implementation of legislative elections by 2014 has been implemented in accordance with laws related legislation. But still found plenty of problems and constraints then then researchers will lift a thesis with the title of the study